Amino Acids and Peptide-Based Supramolecular Hydrogels for Three-Dimensional Cell Culture - Dou, Xiao-Qiu (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.